Psychometric Impact of Diabetic Retinopathy-Induced Visual Impairment: A Hospital-Based Study, Al Buraimi, Sultanate of Oman - Vankudre GS; Mohamed ZD; Ayyappan JP; Alrasheed SH (Clinical Optometry)
Gopi Suresh Vankudre,1 Zoelfigar Dafalla Mohamed,1 Janitha Plackal Ayyappan,1 Saif Hassan Alrasheed2 1Department of Optometry, College of Health Sciences, University of Buraimi, Al Buraimi, Sultanate of Oman; 2Department of Optometry, College of Applied Medical Sciences, Qassim University, Buraydah, Saudi ArabiaCorrespondence: Zoelfigar Dafalla Mohamed, Email abumihad2010@gmail.comBackground: Diabetic retinopathy (DR) posed an adverse psychological impact among affected individuals.Aim: This study evaluates the psychometric impact of Diabetic Retinopathy-induced visual impairment: A hospital-based study, Al Buraimi, Sultanate of Oman.Settings: A hospital-based population having Diabetic Retinopathy, Al Buraimi, Sultanate of Oman.Methods: This cross-sectional, hospital-based study included 218 participants having diabetic retinopathy. The Vision Quality of Life Index (VisQoL) utility questionnaire was used to measure the psychometric status. Ordinal logistic regression analyses evaluated the significant factors from age, gender, visual acuity, duration of DM or DR, responsible for the psychometric status.Results: Of the 218 participants, 114 (52.29%) were males and 104 (47.71%) were females. The mean diabetes mellitus (DM) and diabetic retinopathy duration was 17.21 ± 6.97 years and 5.15 ± 3.51 years respectively. The mean psychometric score was 2.21 ± 1.03. One-third (34.86%), 2.75% of the participants were extremely concerned, while 33.94% were observed to have a little concern. Visual impairment status (p = 0.00), higher age (p = 0.00), DR severity (p = 0.00) and individuals lacking support of the life partner (p = 0.00) were observed to have a significant negative psychometric impact.Conclusion: Majority of the participants had proliferative diabetic retinopathy. A majority of the (34.86%) reported no concern, and a notable percentage (65.14%) expressed a minor-to-severe level of concern. Age, marital status, severity of diabetic retinopathy and level of visual impairment were the significant predictors for their psychometric scores.Keywords: diabetes mellitus, diabetic retinopathy, quality of life, public health, psychological status